Dexras1 interacts with FE65 to regulate FE65-amyloid precursor protein-dependent transcription. - MCLOUGHLIN, DECLAN (American Society for Biochemistry and Molecular Biology, 2008)
FE65 is an adaptor protein that binds to and forms a transcriptionally active complex with the -secretase-derived amyloid precursor protein (APP) intracellular domain. The regulatory mechanisms of FE65-APP-mediated transcription are still not clear. In this report, we demonstrate that Dexras1, a Ras family small G protein, binds to FE65 PTB2 domain and potently suppresses the FE65-APP-mediated transcription. The suppression is not via competition for binding of FE65 between Dexras1 and APP because the two proteins can simultaneously bind to the FE65 PTB2 domain. Phosphorylation of FE65 tyrosine 547 within the PTB2 domain has been shown to enhance FE65-APPmediated transcription but not to influence binding to APP. Here we find that this phosphorylation event reduces the binding between Dexras1 and FE65. We also demonstrate that Dexras1 inhibits the FE65-APP-mediated transcription of glycogen synthase kinase 3 (GSK3). Moreover, small interfering RNA knockdown of Dexras1 enhances GSK3 expression and increases phosphorylation of Tau, a GSK3 substrate. Thus, Dexras1 functions as a suppressor of FE65-APP-mediated transcription, and FE65 tyrosine 547 phosphorylation enhances FE65-APP-mediated transcription, at least in part, by modulating the interaction between FE65 and Dexras1. These findings reveal a novel regulatory mechanism for FE65-APP-mediated signaling.
PUBLISHED
Keywords: Psychiatry